Learning to Read Interacts with Children's Spoken Language Fluency. Issue 2 (3rd April 2022) - Popescu, Anisia; Noiray, Aude
ABSTRACT: Until at least the end of adolescence, children articulate speech differently than adults. While this discrepancy is often attributed to the maturation of the speech motor system, we sought to demonstrate that the development of spoken language fluency is shaped by complex interactions across motor and cognitive domains. In this study, we specifically tested for a relationship between reading proficiency and coarticulatory organization, a fundamental correlate of spoken language fluency, used for both reading aloud and conversational speech. We conducted reading assessments and ultrasound-based kinematic measurements of intersegmental coarticulation in a group of 32 German children. In German, a language which supports rather consistent grapheme-to-phoneme relationships, reading aloud uses similar phoneme to speech motor gesture correspondences as well as coarticulatory mechanisms as conversational speech. Using general additive modeling we found that better readers exhibited lower degrees of intersegmental coarticulation than poorer readers. This study therefore provides evidence that reading proficiency interacts with coarticulatory patterns in beginning readers. It suggests that in addition to maturational factors, interactions between speech motor ability and other co-developing skills must be considered to fully account for spoken language fluency.